(untitled) (Historia, 2021)
Never before in human history have so many animals been subjected to horrific slaughter, unconscionable abuse, and unthinkable living conditions These conditions have a unique history that requires both material and philosophical analysis, and it is a history that needs to be attended to in its specificity so that we might learn better how to transform it. 1 Thus Matthew Calarco in his contribution to Paola Cavalieri’s collection, The Death of the Animal (2009). Running through the conversations comprising this book is a thread of dissention at the Socratic, rationalistic approach taken by analytic philosophy to the question of rights for animals.